Pendidikan Kristiani Kontekstual dengan Pedekatan Dialogue of Being dalam Membangun Kebersamaan sebagai Anak Bangsa - Yermia Tri Putri; Suhadi Suhadi (SIKIP: Jurnal Pendidikan Agama Kristen, 2021)
This research writes about contextual Christian education with a dialogue of being approached to create togetherness as children of the nation. This study uses a qualitative method with specificity to the literature review. Through the dialogue of being approached, the current dialogue approach, the achievement of togetherness as a child of the nation. The main problems of the diversity of the Indonesian people are, among others: inter-ethnic conflict, inter-racial conflict, inter-religious conflict, and inter-group conflict. Contextual Christian Education with a dialogue of-being approach helps Christian educators to educate students to become students who can be present amid society to be light and salt in the spirit of togetherness to create unity and oneness. Through a contextual critical education approach with a dialogue being approached, several conclusions were obtained. First, Christian education must be designed contextually to make it easier for students to understand every content taught. Second, Jesus is a great teacher who also teaches contextually. Third, contextual Christian education is understood in various principles, including the following: a) Christian education must be adapted to the context of the conditions of the people in Indonesia who hold fast to togetherness and diversity but uphold unity and unity b) Contextual Christian education must be accepted in all circles. Age. c) Christian education is not rigid but dynamic, implementing, and applicable. d) Contextual Christian education must provide radical transformation and change.  AbstrakPenelitian ini menulis tentang Pendidikan Kristiani kontekstualitas dengan pendekatan dialog of being-dialog menjadi- demi terciptanya kebersaamaan sebagai anak bangsa. Penelitian ini menggunakan metode kualitatif dengan sepesifik kepada kajian pustaka. Melalui pendekatan dialog of being, pendekatan dialog yang kekinian, maka tercapainya kebersamaan sebagai anak bangsa. Masalah utama keberagaman  bangsa Indonesia adalah antara lain: konflik antar suku, konflik antar ras, konflik antar agama, konflik antar golongan. Pendidikan Kristiani Kontekstual dengan pendekatan dialog of being, menolong para pendidik Kristen untuk mendidik anak didik menjadi siswa-siswi yang dapat hadir ditengah masyarakat menjadi terang dan garam didalam semangat kebersamaan menciptakan persatuan dan kesatuan. Melalui pendekatan Pendidikan kritiani kontekstual  dengan pendekatan dialog of being, maka diperoleh beberapa kesimpulan antara lain: Pertama, Pendidikan Kristen harus didesain secara kontekstual guna memudahkan peserta didik memahami dan mengerti setiap konten yang diajarkan didalamnya. Kedua, Yesus adalah guru sang agung yang juga mengajar secara kontekstual. Ketiga, Pendidikan Kristen yang kontekstual dipahami dalam berbagai prinsip antara lain sebagai berikut: a) Pendidikan Kristen harus disesuaikan dengan konteks kondisi masyarakat di Indonesia yang memegang teguh kebersamaan dan keberagaman namun menjunjung kesatuan dan persatuan b) Pendidikan Kristen kontekstual harus dapat di terima di semua kalangan usia. c) Pendidikan Krsten adalah Pendidikan yang tidak kaku, tetapi Pendidikan yang dinamis, impelementasi dan aplikatif. d) Pendidikan Kristen kontekstual harus memberikan trasnformasi dan  perubahal yang radikal.  Pendidikan Kristiani Kontekstual; Dialogue of being;Kebersamaan anak bangsa